Escherichia coli Can Eat DNA as an Excellent Nitrogen Source to Grow Quickly - Huang, Lili; Zhang, Yehui; Du, Xinmei; An, Ran; Liang, Xingguo (Frontiers in Microbiology, 2022)
Is DNA or RNA a good nutrient? Although scientists have raised this question for dozens of years, few textbooks mention the nutritional role of nucleic acids. Paradoxically, mononucleotides are widely added to infant formula milk and animal feed. Interestingly, competent bacteria can bind and ingest extracellular DNA and even integrate it into their genome. These results prompt us to clarify whether bacteria can “eat” DNA as food. We found that E. coli can grow well in the medium with DNA as carbon and nitrogen sources. More interestingly, in the presence of glucose and DNA, bacteria grew more rapidly, showing that bacteria can use DNA as an excellent nitrogen source. Surprisingly, the amount of DNA in culture media decreased but its length remained unchanged, demonstrating that E. coli ingested long DNA directly. The gene expression study shows that E. coli mainly ingests DNA before digestion and digests it in the periplasm. Bifidobacterium bifidum can also use DNA as the nitrogen source for growth but not efficiently as E. coli. This study is of great significance to study DNA metabolism and utilization in organisms. It also lays a foundation to understand the nutritional function of DNA for intestinal flora and human health.